Identifikasi Jenis Bakteri pada Luka Kaki Diabetik (LKD) berdasarkan Lama Menderita Luka - Risnawati R Risnawati R; Saldy Yusuf; Yuliana Syam (Jurnal Kesehatan Manarang, 2018)
Prevalence of diabetic increased causes many comorbidities that appear like diabetic foot ulcers. Diabetic foot ulcers are a common complication of DM that has shown an increasing trend over the past decade. Diabetic foot ulcers is an open wound on the skin surface due to complications that can develop into infection. The ulcer becomes the entrance gate of bacteria that includes Gram positive bacteria and Gram negative aerobs that spread rapidly and cause tissue damage. The purpose of this study was to identify the type of bacteria in diabetic foot ulcers based on long-standing diabetic foot ulcers. This study was a descriptive observational study, with cross sectional design study conducted by taking swab samples from diabetic foot ulcers. Research respondents were 20 patients with diabetic foot ulcers who did wound care at wound clinic and RSUP Dr Wahidin Sudirohuosodo Makassar. This research is done by Accidental Sampling, the data is analyzed descriptively. Gram stain examination results showed that the identification of bacterial species based on long periods suffered from diabetic foot ulcers with onset <6 months, the dominant bacterial colony was Proteus Mirabilis, 5 respondents (50.0%). And identification of bacterial type based on long suffered diabetic foot injury with onset >6 months, showed colony bacterium that was dominant found was Staphylococcus aureus that is 3 respondent (30.0%). Based on the results of the study of bacterial identification in wounded diabetic foot ulcer with onset <6 months dominated by gram-negative bacteria and identification of bacteria in wounded diabetic foot injuries with onset> 6 months dominated by gram-positive bacteria. Suggestions for further research are identification of bacterial types based on identification of antibiotic therapy used by respondents.